Lama Pemanasan Metode Vapor Heat Treatment (VHT) dan Pelilinan Untuk Mempertahankan Mutu Pepaya Selama Penyimpanan - Rokhani Hasbullah; Elpodesy Marlisa; Ali Parjito; Edy Hartulistiyoso (PERTETA, 2008)
Horticulture products are host for Tephritidae fruitflies that are considered a quarantine risk by many importing countries. This research was conducted to find out the specific condition for the heat treatment using vapor heat treatment (VHT) method to control pest and diseases of papaya and the fruit quality during storage. Papayas were vapor heat treated at medium temperature of 46.5 0C for 0, 15, and 30 minutes. After the treatment, the fruits were waxed using beeswax of 6 % in concentration and then stored at temperature of 10 0C. The results show that the fruitfly of oriental fruitfly (Bactrocera dorsalis) was completely killed by treating in deep water testing at temperature of 46 0C for 10 minutes or at 43 0C for 30 minutes. The VHT of papaya at fruit core temperature of 45.5-46.0 0C for 15-30 minutes following waxing using beeswax of 6% in concentration was found to be effective to control pest and diseases until 21 days of storage without any visible signs of heat injury and without adversely affecting the quality of the fruit. Keywords: Papaya, vapor heat treatment, waxing, quarantine Diterima: 20 Agustus 2007; Disetujui: 24 Nopember 2007